Extensile FSS With Controllable Passband Frequency for EM Transparent Antenna - Xiao-Fan Wang; Ling-Ling Yang; Wen-Wen Yang; Jian-Xin Chen (IEEE Access)
The extensile frequency selective surface (FSS) with controllable passband frequency for electromagnetic (EM) transparent antenna is proposed in this work. In the interleaved scheme array, the low band (LB) antenna casts a shadow over the high band (HB) antenna, resulting in the degradation of the HB radiation performance. The transparent antenna is a good choice as it exhibits bandpass characteristics at the HB while functioning normally at the LB. Moreover, to allow flexible placement of the HB antennas in the array, the LB antenna has to remain transparent to the HB across multiple positions. Given that different combinations of FSS correspond to various placement configurations for HB antennas, an extensible FSS maintaining stable bandpass characteristics from the single unit to the entire LB antenna is proposed. Due to the stable passband frequency of the extensile FSS, the proposed grid-embedded LB antenna presents a satisfactory transparent effect at three representative locations. Besides, the HB radiation recovery and LB working performance can be independently controlled, showing high design efficiency. Subsequently, the array consisting of the grid-embedded transparent LB antenna, $2× 1$ HB array is fabricated. Experimental results show that the array covers the bands of 1.7-2.7 GHz and 3.3-3.8 GHz with stable performance, and the blockage effect is significantly suppressed.